Collaborative editing over opportunistic networks. (22nd February 2022) - Alsulami, Noha; Cherif, Asma; Imine, Abdessamad
Fostered by the high availability of mobile devices and the maturity of wireless communications, opportunistic networks (OppNets) raise a challenging issue on how to share data efficiently without relying on fixed network infrastructure. Most of the current research works focus only on message routing and data dissemination. However, few research works consider the deployment of collaborative applications over opportunistic networks specifically for sharing immutable data (e.g., photos/video files). Thus, sharing mutable data in collaborative editing works with opportunistic communication remains an open issue. Collaborative editors rely on protocols that allow many users to concurrently edit replicated shared documents (e.g., text and multimedia documents) while enforcing the convergence of all replicas. In this paper, we investigate the adaptation of an existing operational transformation-based synchronisation protocol to be deployed over OppNets. For the message delivery between communicating users/nodes, we compare the efficiency of the most known routing protocols in OppNets, PRoPHET, and Epidemic, through simulations in terms of data convergence preservation. We show how the behaviour of each routing protocol impacts the convergence of shared data. From our experimental evaluation, it turns out that PRoPHET outperforms Epidemic in achieving convergence.